Effect of Carcass Chilling on the Palatability Traits and Safety of Fresh Red Meat. Issue 6 (9th September 2019) - Zhang, Yimin; Mao, Yanwei; Li, Ke; Luo, Xin; Hopkins, David L.
Abstract: Chilling procedures have been widely used in livestock abattoirs since the development of refrigeration systems. The major criteria when applying chilling regimes is not only complying with regulations, but economic concerns, and also meat safety and quality assurance requirements. Given recent developments, an updated review is required to guide the industry to choose the best chilling method and to inspire the development of new approaches to chilling. Thus in this paper, the quality and microbial safety of beef, lamb, pork, venison, and bison resulting from different chilling treatments has been reviewed, as well as the underlying mechanism(s) for the different impacts on meat quality traits as a result of different chilling regimes. The effect of fast chilling on the tenderness of beef and lamb is a focus, as some new findings, have recently been reported, while multistep chilling is highlighted as it incorporates the advantages of fast chilling to reduce carcass weight loss, resulting in similar quality improvements as found with slow chilling. It is, suggested, that if spray chilling can be combined with the second phase of multi‐step chilling, it will benefit the meat industry in terms of both meat quality and safety. Future studies should focus on combinations of chilling methods with new technologies, such as medium voltage electrical stimulation, muscle stretching, or ultrasound and so on, to move meat quality and safety to a new level.